Effects of diet and social status on white matter integrity in female cynomolgus monkeys. (1st February 2022) - Kim, Jeongchul; Barcus, Richard A.; Frye, Brett M.; Lockhart, Samuel N.; Craft, Suzanne; Register, Tom; Andrews, Rachel N.; Appt, Susan E.; Vitolins, Mara Z.; Uberseder, Beth; Chen, Haiying; Corbitt, Sarah E.; et al.
Abstract: Background: Mounting evidence suggests that diet may influence risk for cognitive impairment and neurodegenerative disease, including Alzheimer's disease. Nonhuman primates are important models of cognitive aging and Alzheimer's disease‐like neuropathology given their complex central nervous systems and susceptibility to diet‐induced diseases. Diffusion magnetic resonance imaging (MRI) studies in humans report age‐related increases in mean diffusivity (MD) and decreases in fractional anisotropy (FA). Whether nonhuman primate models of Alzheimer's disease‐like neuropathology show similar changes in diffusivity, and whether diet affects these changers is unknown. As such, the purpose of this study was to determine the longitudinal effects of diet (Mediterranean vs Western) and social subordination stress on diffusion MRI measures of white matter structural integrity in a nonhuman primate model of aging. Method: In this IACUC approved study, thirty‐seven middle‐aged cynomolgus monkeys ( Macaca fascicularis ) were evaluated longitudinally with diffusion MRI measures (FA, MD, axial diffusivity [AxD], and radial diffusivity [RD]). Monkeys were scanned at baseline and after 31 months of diet consumption (∼ equivalent to a 9‐year follow up in humans). Diffusion MRIs were preprocessed (corrected for eddy current and geometric distortion) and co‐registered to high resolution T1w MRI to derive diffusion measures. For statistical analyses, cerebral white matter and 9 bilateral regions of interest (ROIs) were selected from NeuroMaps nonhuman primate atlas. Statistical analyses were performed with repeated measures analysis of variance. Result: We observed social status differences in frontal ( p =0.021) and occipital ( p =0.029) white mater ROIs, with greater longitudinal increase or smaller longitudinal decrease in FA among subordinates compared to dominants. Diet and social status interacted to impact AxD in the genu of the corpus callosum (p=0.028). Finally, subordinates in the Mediterranean group demonstrated greater longitudinal diffusivity increases compared to 1) dominants in the Mediterranean group, 2) dominants in the Western group, and 3) subordinates in the Western group (Figure below). Conclusion: While the biological mechanisms underlying these findings require future investigation, our observations suggest that diet and social subordination stress illicit changes in structural white matter integrity that could modify vulnerability to Alzheimer's disease‐like neuropathology in middle‐aged nonhuman primates.